FBXL4-Related Mitochondrial DNA Depletion Syndrome 13 (MTDPS13): A Case Report With a Comprehensive Mutation Review - Ballout, Rami A.; Al Alam, Chadi; Bonnen, Penelope E.; Huemer, Martina; El-Hattab, Ayman W.; Shbarou, Rolla (Frontiers in Genetics, 2019)
Mitochondrial DNA depletion syndromes (MTDPS) are a group of rare genetic disorders caused by defects in multiple genes involved in mitochondrial DNA (mtDNA) maintenance. Among those, FBXL4 mutations result in the encephalomyopathic mtDNA depletion syndrome 13 (MTDPS13; OMIM #615471), which commonly presents as a combination of failure to thrive, neurodevelopmental delays, encephalopathy, hypotonia, and persistent lactic acidosis. We report here the case of a Lebanese infant presenting to us with profound neurodevelopmental delays, generalized hypotonia, facial dysmorphic features, and extreme emaciation. Whole-exome sequencing (WES) showed the girl as having MTDPS13 with an underlying FBXL4 missense mutation that has been previously reported only twice in unrelated individuals (c.1303C > T). Comprehensive literature search marked our patient as being the 94th case of MTDPS13 reported to date worldwide, and the first from Lebanon. We include at the end of this report a comprehensive mutation review table of all the pathological FBXL4 mutations reported in the literature, using it to highlight, for the first time, a possible founder effect of Arab origins to the disorder, being most prevalent in patients of Arab descent as shown in our mutation table. Finally, we provide a direct comparison of the disorder's clinical manifestations across two unrelated patients harboring the same disease-causing mutation as our patient, emphasizing the remarkable variability in genotype-to-phenotype correlation characteristic of the disease.